2011
DOI: 10.1159/000327571
|View full text |Cite
|
Sign up to set email alerts
|

Oral Branched-Chain Amino Acid Granules Reduce the Incidence of Hepatocellular Carcinoma and Improve Event-Free Survival in Patients with Liver Cirrhosis

Abstract: Background: It has been reported that branched-chain amino acid (BCAA) supplementation can improve nutritional status and prevent liver-related complications in patients with decompensated cirrhosis. We investigated the effects of oral BCAA supplementation on the incidence of hepatocellular carcinoma (HCC) and liver-related events in patients with compensated and decompensated cirrhosis. Methods: We enrolled 211 patients with cirrhosis including 152 patients with Child-Pugh A cirrhosis, but no history of HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 68 publications
0
44
1
1
Order By: Relevance
“…This result suggested that C-ion RT could be a safe treatment for patients with sarcopenia with similar survival as for patients with non-sarcopenia. Previous report indicate that the improvement of malnutrition by the intervention of a nutrition support team and early physical therapy intervention aimed at improving skeletal muscle mass are considered to improve the survival of patients with sarcopenia (17)(18)(19). There are no fasting duration and postoperative activity restrictions in C-ion RT; thus, nutrition and physical therapy interventions could be initiated from the commencement of treatment without any interruption during C-ion RT.…”
Section: Acute Toxicities In Sarcopenia Patients (N=22)mentioning
confidence: 99%
“…This result suggested that C-ion RT could be a safe treatment for patients with sarcopenia with similar survival as for patients with non-sarcopenia. Previous report indicate that the improvement of malnutrition by the intervention of a nutrition support team and early physical therapy intervention aimed at improving skeletal muscle mass are considered to improve the survival of patients with sarcopenia (17)(18)(19). There are no fasting duration and postoperative activity restrictions in C-ion RT; thus, nutrition and physical therapy interventions could be initiated from the commencement of treatment without any interruption during C-ion RT.…”
Section: Acute Toxicities In Sarcopenia Patients (N=22)mentioning
confidence: 99%
“…Supplementation of BCAA has been reported to improve the nutritional status and prevent hepatic complications in patients with decompensated cirrhosis [13][14][15]. In addition, Hayashi et al [16] reported that BCAA supplementation was associated with a lower incidence of HCC in cirrhosis patients and appeared to prevent liver-related events in C-P class A patients. Furthermore, Harima et al [17] reported that a BCAA-enriched late evening snack improves energy metabolism and glucose tolerance in cirrhosis patients with advanced HCC undergoing HAIC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, oral BCAA supplementation is now recommended in Japanese guidelines as part of the treatment of HCV-related cirrhosis [16]. Similar to the reports mentioned above, Hayaishi et al [17] showed that the event-free survival of patients with Child-Pugh A cirrhosis was better among patients given oral BCAA supplementation than in those without, although the difference did not reach statistical significance. BCAA supplementation has also been reported to be useful as an adjuvant nutritional therapy following hepatectomy and TACE, showing reduced risk of complications and better maintenance of liver function [18,19,20].…”
Section: Branched-chain Amino Acid Granules and Hcc Incidencementioning
confidence: 91%